Strategi Reinventing Government dalam Pengembangan Pariwisata pada Dinas Pariwisata Kota Tanjungpinang - Yana Wardani, Ratika; Subiyakto, Rudi; Okparizan, Okparizan (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2024)
The tourism sector plays a crucial role in economic growth by increasing the country's foreign exchange and creating jobs. Indonesia, with more than 17,000 islands rich in natural and cultural beauty, has great tourism potential. Riau Islands Province, especially Tanjungpinang City, has significant natural and cultural tourism potential. This research aims to analyze the application of the concept of reinventing government in developing Tanjungpinang tourism by increasing management efficiency and innovation in the tourism bureaucracy. This research uses qualitative methods with data collection techniques through observation, interviews and documentation. The research results show that the application of the principles of